Do lixo à solidariedade : avanços e perspectivas na busca de uma nova realidade - Ferreira, Iane Rocha Przewodowska (2007)
The dissertating study about the solidarity economy has the objective to analyze the four unions responsible for the selective municipal garbage collection in Natal. It aims at verifying the consolidation of these unions as solidarity economic undertakings, revealing which progresses they have made, as well as the social and economic insertion of the garbage collectors and their process of conquering citizenship. The referred four unions had been founded and are constituted, in their majority, by collectors coming from the Cidade Nova lixão (big garbage). As it was closed in August 2004, they decided to make a union in order to collecting garbage. As what concerns the methodic and theoretic proceedings, our research has been developed with a critical perspective and a qualitative approach without discarding and quantitative one. The central analytical categories of this paper are: association, work, social exclusion and citizenship. Our research has had three articulated axis which aim was to apprehend the subject, disclosing it. The exposition of the investigative results is subdivided in four chapters. The first one approaches the main aspects of the crisis of the capital and its reflexes in the world of work. Here we deal with the question the structural unemployment coming as a result of the present economic model, the mains changes verified in the Brazilian work market, as well as levels of unemployment affecting the work market in Natal s metropolitan region. The second chapter treats of the origin, concept and revival in Brazil concerning the tradition of thought and cooperative economic organization, which has recovered the central elements of the associative thought and is nowadays studied in Latin America under the name of solidarity economy. The third chapter deals with embodiment of the collectors unions, its history, appearing and development of each union. The fourth chapter presents the relative dimensions of the analysis categories supported in the reports of institutional actors as well as the perception collectors have about the recyclable stuffs, the way they face the daily life and so on, what brings about the contradictions present in their reality. The final comments sum up the main trends and particularities of the unions researched under the light of the solidarity economy and disclose the real perspectives of social and economic insertion of these collectors and the process they follow to conquest social recognition